Therapeutically interchangeable? A study of real‐world outcomes associated with switching basal insulin analogues among US patients with type 2 diabetes mellitus using electronic medical records data. Issue 3 (4th December 2014) - Levin, P.; Wei, W.; Miao, R.; Ye, F.; Xie, L.; Baser, O.; Gill, J.
<x xml:space="preserve">Abstract</x> Aims To evaluate real‐world clinical outcomes for switching basal insulin analogues [insulin glargine (GLA) and insulin detemir (DET)] among US patients with type 2 diabetes mellitus (T2DM). Methods Using the GE Centricity Electronic Medical Records database, this retrospective study examined two cohorts: cohort 1, comprising patients previously on GLA and then either switching to DET (DET‐S) or continuing with GLA (GLA‐C); and cohort 2, comprising patients previously on DET and then either switching to GLA (GLA‐S) or continuing with DET (DET‐C). Within each cohort, treatment groups were propensity‐score‐matched on baseline characteristics. At 1‐year follow‐up, insulin treatment patterns, glycated haemoglobin (HbA1c) levels, hypoglycaemic events, weight and body mass index (BMI) were evaluated. Results The analysis included 13 942 patients: cohort 1: n = 10 657 (DET‐S, n = 1797 matched to GLA‐C, n = 8860) and cohort 2: n = 3285 (GLA‐S, n = 858 matched to DET‐C, n = 2427). Baseline characteristics were similar between the treatment groups in each cohort. At 1‐year follow‐up, in cohort 1, patients in the DET‐S subgroup were significantly less persistent with treatment, more likely to use a rapid‐acting insulin analogue, had higher HbA1c values, lower HbA1c reductions and lower proportions of patients achieving HbA1c <7.0 or <8.0% compared with patients in the GLA‐C subgroup, while hypoglycaemia rates and BMI/weight values and change from baseline were similar in the two subgroups. In cohort 2, overall, there were contrasting findings between patients in the GLA‐S and those in the DET‐C subgroup. Conclusions This study showed contrasting results when patients with T2DM switched between basal insulin analogues, although these preliminary results may be subject to limitations in the analysis. Nevertheless, this study calls into question the therapeutic interchangeability of GLA and DET, and this merits further investigation.